2017
DOI: 10.1021/acs.energyfuels.7b01140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CaO and CaCO3 on Heavy Metal Capture in Bottom Ash during Municipal Solid Waste Combustion under a CO2/O2 Atmosphere

Abstract: Experiments were conducted to investigate the influence of CaO and CaCO3 on the capture efficiency of heavy metals during the combustion of municipal solid waste (MSW) in CO2/O2 and N2/O2 atmospheres. Six heavy metal elements were studied in this paper, including Pb, Cd, Cu, Cr, Ni, and Zn. On the basis of the results, the operating temperature has a great effect on the transformation of Pb and Cd, while the amount of Cu, Cr, and Ni in the bottom ash are affected only slightly by changes in the temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This is consistent with observations of Tang et al [78] adding CaO or CaCO 3 to MSW and evaluating Cd retention in bottom ash. At 700 • C-800 • C, some (moderate) capture of Cd in bottom ash was observed, whereas at 900 • C the release of Cd from bottom ash was even enhanced, due to experimental temperature exceeding the optimal temperature range of 500 • C-650 • C (releasing retained Cl back).…”
Section: Indirect Chlorination By Pvc and Interactions With Calcareousupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with observations of Tang et al [78] adding CaO or CaCO 3 to MSW and evaluating Cd retention in bottom ash. At 700 • C-800 • C, some (moderate) capture of Cd in bottom ash was observed, whereas at 900 • C the release of Cd from bottom ash was even enhanced, due to experimental temperature exceeding the optimal temperature range of 500 • C-650 • C (releasing retained Cl back).…”
Section: Indirect Chlorination By Pvc and Interactions With Calcareousupporting
confidence: 93%
“…Results from recent studies indicate that the presence of PVC during the combustion/incineration of coal/waste with Cd increases its volatility and potential fractions released in emissions. Calcareous additives could suppress this unfavorable effect; but if added directly into the furnace, the temperature is usually too high for efficient retention of chlorination agents [43,52,68,78,79]. However, if limestone is applied within a semi-dry spray tower, good Cd retention results were achieved, which was documented by Chen et al [57].…”
Section: Indirect Chlorination By Pvc and Interactions With Calcareoumentioning
confidence: 98%
See 2 more Smart Citations
“…Tang et al [53] reported that adding 10% CaO or CaCO 3 to synthetic MSW (flour, paper, wood sawdust, high-density polyethylene (HDPE), textiles, rubber and leather) did not show any increase in the Pb residual rate at 700 • C (i.e., no effect on Pb retention in ash); at 800-1000 • C the residual rate even slightly decreased, even if chlorine was present in these wastes. The results are still consistent with the conclusions of Wang et al [31], stating that the efficient retention temperature of CaO was below 700 • C (at higher temperatures, CaCl 2 can release chlorine back for Pb chlorination).…”
Section: Other Relating Interactionsmentioning
confidence: 99%